Reformasi Keuangan Daerah, Tata Kelola Pemerintahan, Sistem Informasi Keuangan terhadap Pengelolaan Keuangan Daerah serta Implikasinya pada Kinerja Keuangan Pemerintahan Daerah - Ati Rosliyati (Kontigensi : Jurnal Ilmiah Manajemen, 2016)
This study is aimed at identifying and assessing the Effect of Regional Financial Reform, Government Management, and Financial Information System towards Financial Management and its Implications towards the performance of Local Government Finance in East Priangan Region. This study used a descriptive approach and verification by using descriptive survey and explanatory survey. In this study, the sample is SKPD (Work Unit) of 180 regional work units by using path analysis. The study concluded that the effects of the Regional Financial Reform towards the Regional Financial Management is 35.90%, the effect of Government Management towards Regional Financial Management is 30.70%, the effect of the Financial Information System towards regional Financial Management is 35.60%. Simultaneously the effect of independent variables towards Regional Financial Management is 61.10% and the remaining 38.90% is another factor that is not studied but it influenced to the Regional Financial Management. And the last, the Effect of Financial Management towards Financial Performance is 83.90%, while the remaining 29.70% is another factor that is not studied, but also influence.